The Impact of Lower Limb Prosthesis Use on Quality of Life Among Patients with Lower Limb Amputation - Syafi'ie, Hisyam; Ningsih, Cica Trimandasari; Arumsasi, Herwasti (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Lower limb amputation leads to a substantial decline in physical, psychological, and social function, all of which negatively affect an individual’s quality of life (QoL). The use of lower limb prostheses serves as a crucial rehabilitative intervention designed to restore mobility, independence, and psychosocial well-being. Objectives: This study aimed to examine the effect of lower limb prosthesis use on the quality of life of patients with lower limb amputation. Methods: This analytical observational study employed a cross-sectional design involving 30 participants with lower limb amputations residing in the Soloraya region, Indonesia, from January to February 2025. Data were collected using the Orthotics and Prosthetics Users’ Survey (OPUS) QoL subscale, which assesses four domains—physical, psychological, social, and environmental. Data were analyzed using the Shapiro–Wilk test for normality, the Pearson product–moment correlation, and simple linear regression.Results: The data were normally distributed (p > 0.05). A strong positive correlation was observed between the duration of prosthesis use and QoL (r = 0.755, p < 0.001). Simple linear regression revealed that prosthesis use contributed to 57.0% of the variance in QoL among amputees. Conclusion: The use of lower limb prostheses significantly improves the quality of life in individuals following lower limb amputation. Sustainable rehabilitative interventions, continuous user education, and equitable access to orthotic– prosthetic services are essential to optimize patient adaptation and long-term well-being. Keywords: Lower limb amputation, Lower limb prosthesis, Quality of life, OPUS, Rehabilitation.